A Review and Future Directions on the Deterioration Evaluation of Concrete Utility Poles - Takayuki Ueno; Hiroki Tamai; Kanoko Yasukawa; Masahiro Haruguchi (Applied Sciences)
Utility poles are widely utilized to support the distribution lines that deliver electricity produced at power stations to users. The need for utility pole maintenance has increased due to aging, and it is considered necessary to suggest standards and inspection methods for efficient maintenance. To improve the efficiency of pole maintenance, it is essential to organize the deterioration process and replacement indicators based on the structural dynamics of utility poles and suggest methods for evaluating deterioration using non-destructive testing. This paper summarizes previous technical trends and future issues regarding the efficient maintenance of utility poles by summarizing existing standards and research regarding deterioration factors, dynamic characteristics, and evaluation methods. As a result, for more efficient concrete utility pole maintenance, it is essential to collect data regarding the ultimate states of poles subjected to cyclic wind and earthquake loading over a long time and to analyze the correlation between the degree of damage and the data obtained by non-destructive inspection.